Duration of death investigations that proceed to inquest in Australia. Issue 5 (19th July 2016) - Studdert, David M; Walter, Simon J; Kemp, Celia; Sutherland, Georgina
Abstract : Background: Recent government inquiries in several countries have identified the length of time it takes coroners to investigate deaths due to injury and other unnatural causes as a major problem. Delays undermine the integrity of vital statistics and adversely affect the deceased's family and others with interests in coroners' findings. Little is publicly known about the extent, nature and causes of these delays. Methods: We used Kaplan–Meier estimates and multivariable regression analysis to decompose the timelines of nearly all inquest cases (n=5096) closed in coroners' courts in Australia between 1 January 2007 and 31 December 2013. Results: The cases had a median closure period of 19.0 months (95% CI 18.4 to 19.6). Overall, 70% of cases were open at 1 year, 40% at 2 years and 22% at 3 years, but there was substantial variation by jurisdiction. Adjusted analyses showed a difference of 22 months in the average closure time between the fastest and slowest jurisdictions. Cases involving deaths due to assault (+12.2 months, 95% CI 7.8 to 17.0) and complications of medical care (+9.0 months, 95% CI 5.5 to 12.3) had significantly longer closure periods than other types of death. Cases that produced public health recommendations also had relatively long closure periods (+8.9 months, 95% CI 7.6 to 10.3). Conclusions: Nearly a quarter of inquests in Australia run for more than 3 years. The size of this caseload tail varies dramatically by jurisdiction and case characteristics. Interventions to reduce timelines should be tried and carefully evaluated.